A new prediction strategy for long local protein structures using an original description - Bornot, Aurélie (Wiley-Liss, 2009)
A relevant and accurate description of three-dimensional (3D) protein structures can be achieved by characterising recurrent local structures. In a previous study, we developed a library of 120 3D structural prototypes encompassing all known 11- residues long local protein structures and ensuring a good quality of structural approximation. A local structure prediction method was also proposed. Here, overlapping properties of local protein structures in global ones are taken into account in order to characterize frequent local networks. At the same time, we propose a new long local structure prediction strategy which involves the use of evolutionary information coupled with Support Vector Machines (SVMs). Our prediction is evaluated by a stringent geometrical assessment. Every local structure prediction with a Cα RMSD less than 2.5 Å from the true local structure is considered as correct. A global prediction rate of 63.1% is then reached, corresponding to an improvement of 7.7 points compared to the previous strategy. In the same way, the prediction of 88.33% of the 120 structural classes is improved with 8.65 % mean gain. And 85.33% of proteins have better prediction results with a 9.43 % average gain. An analysis of prediction rate per local network also supports the global improvement and gives insights into the potential of our method for predicting super local structures. Moreover, a confidence index for the direct estimation of prediction quality is proposed. Finally, our method is proved to be very competitive with cutting-edge strategies encompassing three categories of local structure predictions.